2013
DOI: 10.1002/hbm.22382
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic causal modeling of load-dependent modulation of effective connectivity within the verbal working memory network

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link AbstractNeuroimaging studies have consistently shown that working memory (WM) tasks engage a distributed neural network that primarily includes the dorsolateral prefrontal (DLPFC), the parietal (PAR) and the anterior cingulate cortices (ACC). The current challenge is to provide a mechanistic account of the changes observed in regional activity. To achieve this we cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
69
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 41 publications
13
69
1
Order By: Relevance
“…Successful maintenance of information in working memory is associated with increased cortical phase synchronization [9,14,15]. From a neurophysiological point of view, in both verbal and visuospatial working memory tasks, the bilateral prefrontal (PFC) and posterior parietal (PPC) cortices are activated [16][17][18]. Theta phase synchronization during a working memory task is sustained during encoding, maintenance, and retrieval between these two anatomical regions and increases with memory load (difficulty of the task) [9,19].…”
Section: Introductionmentioning
confidence: 99%
“…Successful maintenance of information in working memory is associated with increased cortical phase synchronization [9,14,15]. From a neurophysiological point of view, in both verbal and visuospatial working memory tasks, the bilateral prefrontal (PFC) and posterior parietal (PPC) cortices are activated [16][17][18]. Theta phase synchronization during a working memory task is sustained during encoding, maintenance, and retrieval between these two anatomical regions and increases with memory load (difficulty of the task) [9,19].…”
Section: Introductionmentioning
confidence: 99%
“…The intervention aims to enhance cognitive control of emotional information processing by specifically targeting abnormal activation patterns in dlPFC and amygdala that underlie the cognitive control and emotion regulation impairments observed in MDD. To accomplish this, the intervention combined working memory and facial affect identification tasks, which have been shown to specifically target activity in the dlPFC [72] and amygdala [73], respectively. The task performed during the intervention requires that patients identify the emotions expressed on a series of faces displayed on a computer screen while remembering the specific sequence of faces.…”
Section: Neuroplasticitymentioning
confidence: 99%
“…There have been a number of recent studies investigating WM in a DCM framework. report task--related increase in directed connectivity from posterior parietal cortex to inferior frontal cortex and middle frontal gyrus and similarly, Dima et al (2014) found WM--load increases in connectivity from right PC to right dlPFC.…”
Section: Introductionmentioning
confidence: 71%
“…The modulation of the forward connection contrasts with the modulation of the backward connection seen by . Dima et al (2014) similarly see increased connectivity from PC to dlPFC, using a verbal N--Back WM task, and using DCM to model the activity of bilateral PC, dlPFC and ACC.…”
Section: Brain Functional Connectivity and Working Memorymentioning
confidence: 81%
See 1 more Smart Citation